PRACOWNICZE PRAWO POWSTRZYMANIA SIĘ OD WYKONYWANIA PRACY WYMAGAJĄCEJ SZCZEGÓLNEJ SPRAWNOŚCI PSYCHOFIZYCZNEJ - Jankowiak, Jarosław (Wydział Prawa i Administracji UAM, 1998)
The author - on the basis of the article 240 § 4 of the Labour Code - discusses the problem of the right serving all employed persons to abstain from undertaking a job that needs special skills of physical and/or psychological nature. Among others pilots, engine-drivers, drivers, lift operators, naval pilots, etc., are concerned with this problem. The author analyses also relations between the present labour law and medical opinions (including reports issued by psychologists) and, as well, the question of legal responsibility of an employee for the acts that were done under the lack of such skills. The question of prophylactic examinations was also presented together with legal provisions that regulate adequate proofs.
THE RIGHT OF AN EMPLOYEE TO ABSTAIN HIMSELF FROM UNDERTAKING A JOB THAT NEEDS SOME SPECIAL PHYSICAL AND/OR PSYCHOLOGICAL SKILLS